SMS-Diff: Physics-aware spectral-spatial diffusion for unified geospatial multi-modal reconstruction - Wenzheng Zhang; Zhanlong Chen; Mengxi Zhang; Chenxing Sun; Run Wang; Jincheng Shuang; Junli Zhao (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Sphagnum trait-mediated service function in response to phosphorus and nitrogen dynamics on the karst plateau - Chengyi Li; Run Liu; Mingzhu He; Jiachen Shen; Zhaohui Zhang; Qimei Wu; Dengfu Wang; Hong Sun (Forest Ecology and Management, 2026)

Lignin-first depolymerization of softwood over a NiCu/TiO2 catalyst for the sustainable production of dihydroconiferyl alcohol - Peng Zhu; Yu-Xin Zhang; Qiang Wang; Guo-Hui Cheng; Jun-Li Ren; Ling-Ping Xiao; Run-Cang Sun (Bioresource Technology, 2026)

Bacterial co-culture significantly enhanced polyethylene biodegradation - Qiang Liu; Yuzhi Sun; Pen Jin; Liang Shen; Run Hu; Lisha Song; Yanjiao Qi; Zhenbin Chen; Hong Zhang (Journal of Environmental Chemical Engineering, 2026)

Experimental investigation on adiabatic two-phase frictional pressure drop of R32, R1234ze(E), and their mixtures in a horizontal minichannel - Na Liu; Yeyi Liu; Hao Ji; Dezheng Sun; Run Li; Chuandian Dong; Huan Lin (International Journal of Refrigeration, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Structural features of endogenous polyphenols in modulating oxidative stability of tiger nut (Cyperus esculentus L.) oil: Insights from Rancimat and density functional theory - Zheng-Kai Zhang; Meng-Chen Xie; Jun-Chao Zhang; Lu-Han Sun; Xiao-Shuang Cai; Run-Yang Zhang; Guo-Qiang Zhang; Hua-Min Liu (Food Chemistry, 2026)

Experimental and numerical investigation into the interfacial performance of Fe-SMA strips bonded to cold-formed steel C-section substrates - Hai-Tao Wang; Wen Su; Han-Ying Qi; Zhiqiang Dong; Xinliang Sun; Run-Ze Zhu (Engineering Structures, 2026)

The lnc40545-miR-965-CYP307A1 regulation pathway mediates imidacloprid resistance in Rhopalosiphum padi (L.) - Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Yong Sun; Dong-Mei Chen; Fan-Bin Kong; Run-Qiang Liu; Hai-Hong Gu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Impacts of extreme drought events on forest ecosystem resilience in mainland Southeast Asia - Lusha Ma; Kun Yang; Zongqi Peng; Run Sun; Mingfeng Zhang; Danni Su; Jingcong Ma; Yanhui Zhu; Xianchun Pan (Science Bulletin, 2026)

Assessing climate-driven shifts in mariculture across coastal China: Implications for sustainable management and conservation - Yanwei Sun; Ying Li; Run Wang; Xuewei Hou; Renfeng Ma (Regional Studies in Marine Science, 2026)

Boosting char formation in lignin aerogels via PN synergy: A route to flame retardancy and multifunctional performance - Jia-Hui Wang; Tao Gui; Shuang-Lin Zou; Qing-Hua Wang; Ying-Chun Xu; Rong Tan; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2026)

Galacto-oligosaccharides enrich galactosidase-encoded rather than all Lachnospiraceae bacteria to redress abnormal gut microbiota and lipid metabolism in pregnancy - Rujun Wei; Jiyun Long; Haoxue Xia; Yanni Sun; Lin Zhang; Xiaoqing Li; Hongping Zhang; Run Wang; Shengtao Gao; Yunwei Chen; Yun Gu; Xiaoya Wang; et al. (Science China Life Sciences, 2026)

Remediation strategies of plastics contaminated soils based on novel bacterial communities: Enhancing plastic degradation and element cycling - Qiang Liu; Yuzhi Sun; Pen Jin; Liang Shen; Run Hu; Lisha Song; Yanjiao Qi; Zhenbin Chen; Hong Zhang (Chemical Engineering Journal, 2026)

CARE: a next-generation high resolution cloud and radiation remote sensing product and its Earth system applications - Husi Letu; Huazhe Shang; Run Ma; Chong Shi; Takashi Y. Nakajima; Hiroshi Ishimoto; Jérôme Riedi; Lesi Wei; Ri Xu; Dabin Ji; Qixiang Sun; Sude Bilige; et al. (Science Bulletin, 2026)

Experimental study on spray-induced fouling on the outer surface of heat exchangers - Liansheng Liu; Hangkai Liu; Yuhui Li; Run Sun; Xuanchen Liu (Process Safety and Environmental Protection, 2026)

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Experimental investigation on adiabatic two-phase frictional pressure drop of R290, R600a, and their mixtures in a horizontal minichannel - Na Liu; Hao Ji; Yeyi Liu; Run Li; Dezheng Sun; Qian Zhao; Jianxiang Guo (International Journal of Refrigeration, 2026)

Investigating the failure mechanism of a landslide triggered by the combined effects of excavation and rainfalls through numerical approaches - Shu-wei Sun; Xin-yu Fu; Yuan Li; Qiang Wen; Run-jie Gong (Landslides, 2026)

Chloride Loss in Fine Aerosols over the Atmosphere of Pearl River Estuary - Yuan Gao; Jianbo Ye; Lili Ming; Run Lu; Jiayin Sun; Guizhen Fang; Yawei Xue; Yee Jun Tham (Aerosol Science and Engineering, 2026)

Ultrasensitive detection of α-amanitin using a dual-signal aptasensor based on aptamers selected via a novel MB-GO SELEX strategy - Run Tian; Jiadi Sun; Xinqiang Xie; Wangqiu Deng; Mengyao Zheng; Yongli Ye; Yongwei Feng; Xiulan Sun (Food Bioscience, 2026)

Advanced functionalization strategies of chitin and chitosan toward sustainable nanocomposites - Shuang-Lin Zou; Xin-Ran Liu; Jia-Hui Zhang; Ying-Chun Xu; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Carbohydrate Polymers, 2026)

Alstoniaschines A‒I, nine undescribed alkaloids from Alstonia scholaris and their potential medicinal effects on diabetic nephropathy - Wen-Jie Sun; Shi-Shi Qin; Xian-Run Wu; Yun-Li Zhao; Xu-Jie Qin; Xiao-Dong Luo (Phytochemistry, 2026)

Mechanistic insight into curcumin-induced conjugative plasmid transfer acceleration: Role of intracellular arginine uptake - Min-ge Wang; Kai-di Liu; Wen-jie Jin; Run-bo Li; Jun-qi Liu; Liang-xing Fang; Jian Sun; Xiao-ping Liao (Food Microbiology, 2026)

Anion-modulated Cu8 nanoclusters as high-performance hypergolic fuels enabled by low-concentration oxidizer - Run-Meng Li; Chao Wang; Yan-Wen Chen; Guoqiang Sun; Xiao-Fei Liu; Shuang-Quan Zang (Chemical Engineering Journal, 2026)

Cuproptosis Inhibition by C-Phycocyanin Confers Neuroprotection against Copper-Induced Mitochondrial Damage and Cognitive Impairment - Run Song; Junwan Fan; Jiannan Wu; Shiyi Yin; Ying Zhang; Shihe Jiang; Yan Li; Xin Zhao; Mengjiao Sun; Weina Jin; Wenyan He; Junqiang Yan (Molecular Neurobiology, 2026)

Insights into the combined effect of N2H4 and NH2OH on CANON process in SBR: Nitrogen removal performance, stability of process and microbial community - Zi-Yue Li; Run-Mei Li; Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Zi-Jun Yan; Qian-Qian Zhang; Zai-Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Geological and geochemical characteristics of intermediate-basic intrusions in Funiushan area, southern margin of the North China Craton: Implications for tectonic environment and mantle properties in the Early Cretaceous - Wei Zeng; Feng-Yue Sun; Cheng-Dong Li; Zhi-Dan Li; Yin-Hang Cheng; Wen-Gang Liu; Jia-Run Tu; Chao Zhang; Xing Liu; Wei-Zhi Sun (Lithos, 2025)

A visualization-enhanced electrochemical sensing system with mobile data transmission for rapid 3-monochloropropane-1,2-diol detection - Ni Wu; Xiaojun Wang; Run Xu; Changxia Sun; Xinwei Li; Qiang Li (Food Chemistry, 2025)

Global synthesis of nitrogen management in sugarcane systems: Decoding climate-soil-management drivers of Brazil-China contrasts - Xiaomai Yuan; Shengsen Zhou; Fumin Wei; Li Ma; Yongfeng Sun; Dingjiao Peng; Run Liang; Yibao Luo; Baoshan Chen; Wei Yao; Ziting Wang (Field Crops Research, 2025)

Bond behavior between concrete and thermoplastic GFRP bars with novel surface features - Jun-Jie Zeng; Hou-Qi Sun; Jun-Run Xia; Sheng-Zhao Feng; Bin Zhao; Jie-Kai Zhou; Yan Zhuge (Engineering Structures, 2025)

Dual-gripper coordination effect stabilizing zinc anodes for high-performance zinc metal batteries - Tian-Yi Yang; Kun Li; Ting-Ting Su; Li Ma; Qiu-Shuai Xu; Chang-You Shao; Wen-Feng Ren; Run-Cang Sun (Chemical Engineering Journal, 2025)

Environmental adaptive nanoplatform for bacteriotherapy - Wei Sun; Yang Bai; Xuefei Shao; Bowen Li; Haohua Yuan; Xuheng Chen; Run Yang; Yuan Liu; Shixiang Cheng; Yanguo Xi; Qing-hui Meng; Bin Zheng; et al. (Chemical Engineering Journal, 2025)

pH-regulated structural and interfacial properties of OSA starch/whey protein fiber complexes to improve the storage and digestive stability of citrus essential oil emulsions - Run Ji; Haowen Sun; Zhao Chen; Shuang Song; Hao Guo; Xiuling Zhang; Fei Wu (Carbohydrate Polymers, 2025)

Freeze–thaw impacts on the mechanical behavior of silty clay: Insights from experimental and DEM investigation - Run Liu; Rui Zhang; Ruohan Sun (Bulletin of Engineering Geology and the Environment, 2025)

Construction and optimization of a near-infrared spectroscopic model for the assessment of nitrogen and phosphorus in dairy farm slurry under different temperatures - Mengting Li; Shengbo Liu; Di Sun; Zengjun Yang; Run Zhao; Keqiang Zhang (Computers and Electronics in Agriculture, 2025)

Molecular docking screening of endogenous protease inhibitors in sea bass (Lates calcarifer) and in vitro validation of their inhibitory efficacy - Run-Jian Gao; Lu Sun; Sen-Di Zhou; Yu-Meng Liu; Wei-Qiang Qiu; Sheng-Ping Yang; Yun-Fang Qian (Food Bioscience, 2025)

Bioinspired moist-electric generator with self-protection and autonomous healing enabled by dynamic supramolecular polyurethane - Renquan Xing; Ying Sun; Xiangyi Hou; Jing Yan; Run Wang; Xupin Zhuang; Guang Yang (Chemical Engineering Journal, 2025)

Design of organohydrogels with melt-adjustable mechanics via an “Oil-in-Water” biphasic network synergy for flexible strain sensor applications - Shao-Fei Sun; Wei He; Meng Li; Shaochao Sun; Changyou Shao; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2025)

A strain of Rickettsia induces thelytoky in Anastatus gansuensis via maternal transmission - Run-Na Gong; Yong-Ming Chen; Jun-Bo Luan; Chen-Yi Li; Xiang Sun; Haneef Tariq; Lian-Sheng Zang (Journal of Pest Science, 2025)

A review of pharmacological effects and bioactive constituents of Euonymus alatus - Na Sun; Yujing Wang; Caihong Zhou; Huanhuan Kang; Run Wang; Xiu Feng; Shuo Ma; Linxuan Jin; Xin Zhang; Penghua Shu (Phytochemistry Letters, 2025)

Impact of collagen degradation on the textural quality of salmon (Salmo salar): A preliminary study from the perspective of endogenous collagenase and bacteria - Lu Sun; Run-Jian Gao; Cheng-Jian Shi; Andrew M. Hemmings; Yun-Fang Qian (Food Bioscience, 2025)

A Study of the Global Buckling Response and Control Measures for Snake-Laid Pipelines Under Uneven Soil Resistances - Runnan Miao; Xiang Sun; Chengfeng Li; Run Liu; Xiangning Du; Yinuo Liu (Journal of Marine Science and Engineering, 2025)
The snake-laying method is widely employed as an effective strategy for global buckling mitigation in submarine pipelines. The uneven distribution of soil resistance along pipeline routes significantly amplifies the complexity of global buckling responses in snake-laid pipelines and challenges their control mechanisms. This study establishes a finite element computational model to investigate the effects of soil resistance distribution gradients and patterns along pipeline routes, alongside their coupling with critical snake-laying parameters (spacing, offset, curvature). The research revealed that an uneven distribution of soil resistance can induce the global buckling submersion phenomenon in snake-laid pipelines. Among the critical snake-laying parameters, curvature enhancement proves to be the most effective mitigation strategy against the global buckling submersion phenomenon. Additionally, an improvement in the conventional uniform-laying scheme is proposed for uneven soil resistance distribution: the originally planned snake-laid section can be replaced by a straight pipeline section in the high-resistance zone. This study provides enhanced technical solutions for global buckling prevention in pipelines traversing uneven seabeds.

Characterizing Post-Storm Beach Recovery Modes: A Field-Based Morphodynamic Study from Dongdao Beach, China - Lulu Liu; Yan Sun; Run Liu; Daoheng Zhu; Zhaoguang Chen; Zhiqiang Li (Journal of Marine Science and Engineering, 2025)
The post-storm beach recovery process exhibits variability. Understanding its mechanisms is crucial for advancing the study of beach morphodynamics. This study involved a 25-day continuous field observation on Dongdao Beach, Hailing Island, Yangjiang City, Guangdong Province, following the passage of Typhoon Cempaka. The evolution of beach morphology and the spatiotemporal variations in erosion and accretion were analyzed to explore the key influencing factors, response mechanisms, and recovery modes during the short-term recovery process. The post-storm evolution of beach profile structures is predominantly influenced by major geomorphic units such as berms and sandbars, whereas localized responses are characterized by adjustments of fine-scale features like micro-troughs. The width of the supratidal zone and the position of the berm crest continuously fluctuate, while the slope of the intertidal zone increases or decreases as the berm crest migrates landward or seaward. The erosion–accretion process was complex and occurred in distinct stages, with marked spatial heterogeneity. In some areas, the beach experienced multiple short-term cycles of alternating erosion and accretion. Beach slope plays a significant role in short-term recovery. Three types of response relationships between beach unit-width volume and changes in slope were observed, with flatter beaches being more sensitive to changes in unit-width volume. Based on this, four recovery modes in the post-storm short-term recovery process were explored from the perspective of beach slope. This study provides theoretical support for managing beaches after storms and recommends the implementation of zoned and phased management strategies based on different recovery modes to enhance the efficiency and resilience of coastal recovery.

Study on the lateral breakout resistance of submarine pipelines in the sand wave area - Run Liu; Yinze Guan; Chengfeng Li; Xiang Sun; Yinuo Liu; Zheng Yu (Ocean Engineering, 2025)

Restoration of secondary forest in the Greater Mekong Subregion struggles to offset primary forest carbon losses - Zongqi Peng; Yanhui Zhu; Kun Yang; Yi Luo; Xixi Lu; Jiasheng Wang; Yang Zhang; Danni Su; Run Sun; Mingfeng Zhang; Jingcong Ma; Yang Liu; et al. (Global and Planetary Change, 2025)

Low-temperature catalytic oxidation of toluene using CeO2@MIL-101(Fe): Stability against water and SO2 - David Murindababisha; Abubakar Yusuf; Kien-Woh Kow; Yong Sun; Run Pan; Yong Ren; George Zheng Chen; Jianrong Li; Chengjun Wang; Jun He (Process Safety and Environmental Protection, 2025)

A critical review of human internal exposure to short-chain chlorinated paraffins and its concerning health risks - Ke Fang; Yi-bin Sun; Run-ming He; Jian-kun Qian; Wen Gu; Yi-fu Lu; Zhao-min Dong; Yi Wan; Chao Wang; Song Tang (Environmental Research, 2025)

Mechanochemical treatment boosted microwave-assisted sulfonation of softwood lignin for the fabrication of dye dispersant - Xu Fu; Ling-Ping Xiao; Bo-Wen Meng; Wen-Jie Li; Run-Cang Sun (Chemical Engineering Journal, 2025)

Emission characteristics, environmental impact, and occupational health risks assessment of volatile organic compounds (VOCs) in the hairdressing sector - Run Hao; Xinmiao Lin; Zhen Yao; Meng Wang; Jianling Sun; Hailin Wang (Atmospheric Pollution Research, 2025)

Whole rock and zircon geochemistry of the Tieshan pluton in Daye region, Eastern China: Implication for petrogenesis and Fe-Cu-Au-(Co) mineralization - Bao Zhou; Guang Wen; Run-Jie Zhou; Yue Sun; Chang-Xiong Wu; Jin Zhu; Zhi-Jun Qin; Xiao-Yang Liu; Xiao-Zeng Cheng (Journal of Geochemical Exploration, 2025)

Enhanced H2O2 production via Piezo-photocatalysis using BaTiO3/g-C3N4 S-scheme heterojunction - Ziwei Zhao; Ruixin Chen; Qi Ling; Kui Yan; Wei Gan; Yuqing Lu; Sheng Ding; Run Liu; Zhaoqi Sun; Miao Zhang (Journal of Environmental Chemical Engineering, 2025)

Characterization of β-cyclodextrin inclusion complexes embedded with lemongrass and basil essential oils and their modified sustained-release pads for large yellow croaker (Larimichthys crocea) fillet preservation - Yun-Fang Qian; Cheng-Jian Shi; Lu Sun; Run-Jian Gao; Sheng-Ping Yang (Food Bioscience, 2025)

Multiple active sites of CuO/CeO2 catalysts toward enhanced hydrogenolysis of hardwood lignin into phenolic monomers - Heng Zhang; Ling-Ping Xiao; Qiang Wang; Qian Xu; Run-Cang Sun (Fuel, 2025)

From metabolomics to therapeutics: identifying causal metabolites and potential drugs for the treatment of osteoarthritis - Heng Li; Jingyan Sun; Jiewen Zhang; Yang Chen; Yiwei Zhao; Ruomu Cao; Ning Kong; Xudong Duan; Huanshuai Guan; Run Tian; Kunzheng Wang; Pei Yang (Inflammopharmacology, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Clock bias prediction of navigation satellite based on BWO-CNN-BiGRU-attention model - Wenlong Sun; Jinping Chen; Caibo Hu; Yongxin Lin; Maolei Wang; He Zhao; Run Zhao; Guitao Fu; Tan Zhao (GPS Solutions, 2025)

Biomagnification of polybrominated diphenyl ethers and alternative halogenated flame retardants through food chains of yellowfin tuna (Thunnus albacares) and their prey from the South China Sea and the associated potential health risk - Run-Xia Sun; Chang-Gui Pan; Feng-Jiao Peng; Zhong-Biao Chen; Yue Sun; Jiang-Tao Fan; Jun Zhang; Bi-Xian Mai (Science of The Total Environment, 2024)

Synergistic defects and structural reconstruction in S-scheme Bi2MoO6-x-TiO2 heterojunction for enhancing piezo-photocatalytic degradation of gatifloxacin - Ruixin Chen; Wei Gan; Jun Guo; Sheng Ding; Run Liu; Ziwei Zhao; Kui Yan; Zihan Zhou; Miao Zhang; Zhaoqi Sun (Chemical Engineering Journal, 2024)

A new framework for assessing and dealing with heat risk from an urban resilience perspective - Teng Zhang; Yixuan Sun; Run Wang; Yong Yang; Le Yin; Liangang Li; Baolei Zhang (Journal of Cleaner Production, 2024)

The potential of glycinin basic peptide derived from soybean as a promising candidate for the natural food additive and preservative: A review - Hou-Qi Ning; Hai-Run Fan; Chun-Ling Yang; Gui-Jin Sun; Ying-Qiu Li; Hai-Zhen Mo (Food Chemistry, 2024)

Evidence of polybrominated diphenyl ethers (PBDEs) and alternative halogenated flame retardants (AHFRs) in wild fish species from the remote tropical marine environment, south China sea - Run-Xia Sun; Chang-Gui Pan; Feng-Jiao Peng; Zi-Ling Yu; Hai-Yang Shao; Bing-Zhong Yang; Zhong-Biao Chen; Bi-Xian Mai (Environmental Pollution, 2024)

Biosensors based on cell-free synthetic expression for environmental monitoring and food hazards detection: Principle, design, and application - Tao Liu; Jiadi Sun; Xuran Fu; Yongli Ye; Run Tian; Qi Bao; Mengyao Zheng; Lanlan Zhang; Xiulan Sun (Chemical Engineering Journal, 2024)

Exercise Alleviates Fluoride-Induced Learning and Memory Impairment in Mice: Role of miR-206-3p and PREG - Lei Chai; Qiqi Cao; Ke Liu; Run Zhu; Hao Li; Yanghuan Yu; Jixiang Wang; Ruiyan Niu; Ding Zhang; Bo Yang; Mohammad Mehdi Ommati; Zilong Sun (Biological Trace Element Research, 2024)

Effect of Voluntary Wheel Running on Anxiety- and Depression-Like Behaviors in Fluoride-Exposed Mice - Mengjie Qi; Yue Wu; Han Shi; Jie Liu; Run Zhu; Jixiang Wang; Amna Rafique; Bo Yang; Ruiyan Niu; Ding Zhang; Zilong Sun (Biological Trace Element Research, 2024)

Evaluation of the applicability of beach erosion and accretion index in Qiongzhou Strait of China - Lulu Liu; Yan Sun; Run Liu; Xiaobo Wei; Zhiqiang Li (Frontiers in Marine Science, 2024)
In coastal erosion studies, the erosion and accretion index is a vital research tool for analyzing types of erosion and accretion. This index is primarily empirical or semi-empirical and is usually validated through tank experiments or open beach datasets, resulting in significant variation across different beach environments. In this study, 11 beach profiles of eight beaches measured along the Qiongzhou Strait in China, measured from 2018 to 2021, were analyzed to quantitatively determine coastal erosion or accretion by calculating each profile’s volume change per unit width. Additionally, sediment and wave data were used to calculate five erosion and accretion indices monthly to determine erosion and accretion conditions. These conditions were then compared with actual beach erosion and accretion data to evaluate the applicability of various discriminant indices. Furthermore, optimizing the threshold values of discriminant indices. The results show that: (1) Overall annual erosion and accretion are minimal, but seasonal variation is significant for beaches on both sides of the Qiongzhou Strait; (2) The five discriminant indices have some limitations in this study area, necessitating careful consideration when applying them to headland bay arc-shaped beaches with fetch-limited environments like the Qiongzhou Strait; (3) The selection of discriminant index parameters and their respective contribution degree of each parameter affects the formula’s applicability, with two-parameter formulas proving superior to the three-parameter formula in the study area; (4) Beach environmental factors, particularly those influenced by headlands and fetch-limited environments, impact the indices’ applicability; (5) Increasing the threshold value to a certain extent can improve the formula’s applicability.

Carbon–sulfur–calcium isotopic variability of lower Cambrian shale-hosted carbonate concretions: Insights into growth mechanisms and calcium cycling - Xiqiang Zhou; Xiyuan Chen; Tongxuan Du; Jian Sun; Dongjie Tang; Run Li; Kang-Jun Huang; Yi Ding; Daizhao Chen (Sedimentary Geology, 2024)

Experimental Study on Multistage Seismic Damage Process of Bedding Rock Slope: A Case Study of the Xinmo Landslide - Jing-Jing Tian; Tian-Tao Li; Xiang-Jun Pei; Jian Guo; Shou-Dao Wang; Hao Sun; Pei-Zhang Yang; Run-Qiu Huang (Journal of Earth Science, 2024)

Construction of amphoteric hydrogel electrolytes with charge modification: An investigation of ion migration mechanism and antibacterial property - Shao-Fei Sun; Xiao-Ya Zhao; Ce Gao; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2024)

Plasma Deoxycholic Acid Levels are Associated with Hemodynamic and Clinical Outcomes in Acute Pulmonary Embolism Patients - Na Sun; Yi-Qiang Chen; Yan-Sheng Chen; Lei Gao; Run-Wei Deng; Jing Huang; You-Li Fan; Xuan Gao; Bin-Feng Sun; Na-Na Dong; Bo Yu; Xia Gu; et al. (Cardiovascular Toxicology, 2024)

Tough and biodegradable C-lignin cross-linked polyvinyl alcohol supramolecular composite films with closed-looping recyclability - Tao Gui; Ling-Ping Xiao; Shuang-Lin Zou; Yue Zhang; Xu Fu; Chang-Hao Liu; Run-Cang Sun (Chemical Engineering Journal, 2024)

Structure and dynamics of microbial communities associated with the resurrection plant Boea hygrometrica in response to drought stress - Run-Ze Sun; Yuan-Yuan Wang; Xiao-Qiang Liu; Zhao-Lin Yang; Xin Deng (Planta, 2024)

MiRNA-seq and mRNA-seq revealed the mechanism of fluoride-induced cauda epididymal injury - Yanghuan Yu; Run Zhu; Mengjie Qi; Jie Liu; Kewei Cao; Ding Zhang; Bo Yang; Ruiyan Niu; Jundong Wang; Yangfei Zhao; Zilong Sun (Science of The Total Environment, 2024)

Internal electric field and oxygen vacancies synergistically boost S-scheme VO/BiOCl-TiO2 heterojunction film for photocatalytic degradation of norfloxacin - Ruixin Chen; Wei Gan; Jun Guo; Yuqing Lu; Sheng Ding; Run Liu; Miao Zhang; Zhaoqi Sun (Chemical Engineering Journal, 2024)

Synergistically Augmenting Cancer Immunotherapy by Physical Manipulation of Pyroptosis Induction - Chenyang Zhao; Tingting Zheng; Run Wang; Xiaona Lin; Zhengming Hu; Zhuofei Zhao; Zhifei Dai; Desheng Sun (Phenomics, 2024)
Pyroptosis is a newly recognized type of programmed cell death mediated by the gasdermin family and caspase. It is characterized by the formation of inflammasomes and the following inflammatory responses. Recent studies have elucidated the value of pyroptosis induction in cancer treatment. The inflammatory cytokines produced during pyroptosis can trigger immune responses to suppress malignancy. Physical approaches for cancer treatment, including radiotherapy, light-based techniques (photodynamic and photothermal therapy), ultrasound-based techniques (sonodynamic therapy and focused ultrasound), and electricity-based techniques (irreversible electroporation and radiofrequency ablation), are effective in clinical application. Recent studies have reported that pyroptosis is involved in the treatment process of physical approaches. Manipulating pyroptosis using physical approaches can be utilized in combating cancer, according to recent studies. Pyroptosis-triggered immunotherapy can be combined with the original anti-tumor methods to achieve a synergistic therapy and improve the therapeutic effect. Studies have also revealed that enhancing pyroptosis may increase the sensitivity of cancer cells to some physical approaches. Herein, we present a comprehensive review of the literature focusing on the associations between pyroptosis and various physical approaches for cancer and its underlying mechanisms. We also discussed the role of pyroptosis-triggered immunotherapy in the treatment process of physical manipulation.

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

A DEM-based approach for modeling the thermal-mechanical behavior of frozen soil - Ruohan Sun; Run Liu; Huan Zhang; Rui Zhang; Yu Jiang; Ruilong Yin (European Journal of Environmental and Civil Engineering, 2024)

The antimicrobial effect and mechanism of the Artemisia argyi essential oil against bacteria and fungus - Daoyuan Li; Run Wang; Meng You; Naidong Chen; Li Sun; Naifu Chen (Brazilian Journal of Microbiology, 2024)

Physicochemical properties of clayey deposits slurry treated by lime-activated ISSA and GGBS considering seawater salinity effect - Zhao Sun; Wen-Bo Chen; Run-Dong Zhao; Jiang-Shan Li; Zhen-Yu Yin; Jian-Hua Yin; Yong-Gui Chen (Applied Clay Science, 2024)

Emission characteristics, environmental impact, and health risk assessment of volatile organic compounds (VOCs) during manicure processes - Run Hao; Jianling Sun; Rui Liu; Huan Zhao; Zhen Yao; Hailin Wang; Zhengping Hao (Science of The Total Environment, 2024)

Comparative study on ventilation and air conditioning system schemes based on virus pollution control in hospital infusion room - Weixue Cao; Xudong Zhang; Wanxiang Yao; Run Sun; Yutong Du; Quanbin Shi; Zipeng Li (Aerobiologia, 2023)

Structural plane recognition from three-dimensional laser scanning points using an improved region-growing algorithm based on the robust randomized Hough transform - Zhi-hua Xu; Ge Guo; Qian-cheng Sun; Quan Wang; Guo-dong Zhang; Run-qing Ye (Journal of Mountain Science, 2023)

Manual correction of genome annotation improved alternative splicing identification of Artemisia annua - Zhaoyu Liu; Yupeng Du; Zhihao Sun; Bohan Cheng; Zenghao Bi; Zhicheng Yao; Yuting Liang; Huiling Zhang; Run Yao; Shen Kang; Yuhua Shi; Huihua Wan; et al. (Planta, 2023)

Effect of seawater on solidification/stabilisation treatment of marine soft soil slurry by lime-activated ISSA and GGBS - Zhao Sun; Wen-Bo Chen; Run-Dong Zhao; Peiliang Shen; Jian-Hua Yin; Yong-gui Chen (Engineering Geology, 2023)

DEM investigation of the mechanical behavior of frozen soil along various stress paths - Ruohan Sun; Run Liu; Huan Zhang; Chun Liu; Chengfeng Li (Bulletin of Engineering Geology and the Environment, 2023)

Valorization of lignin through reductive catalytic fractionation of fermented corn stover residues - Wen-Zheng Yin; Ling-Ping Xiao; Shuang-Lin Zou; Wen-Xin Li; Hongliang Wang; Run-Cang Sun (Bioresource Technology, 2023)

Research on the Critical Buckling Pressure of Bucket Foundations with Inner Compartments for Offshore Wind Turbines - Guodong Sun; Run Liu; Qingxin Li; Guoyu Huang; Zhenbo Zhou; Cheng Zhang (Journal of Ocean University of China, 2023)

Forest hydrology modeling tools for watershed management: A review - Ge Sun; Xiaohua Wei; Lu Hao; María González Sanchis; Yiping Hou; Rasoul Yousefpour; Run Tang; Zhiqiang Zhang (Forest Ecology and Management, 2023)

Three-dimensional agricultural water scarcity assessment based on water footprint: A study from a humid agricultural area in China - Yunan Yan; Run Wang; Si Chen; Yu Zhang; Qianli Sun (Science of The Total Environment, 2023)

Trophinin-associated protein expression correlates with shorter survival of patients with glioma: a study based on multiple data fusion analysis - Yong Sun; Zhen Dong Liu; Run Ze Liu; Xiao Yu Lian; Xing Bo Cheng; Yu Long Jia; Bin Feng Liu; Yan Zheng Gao; Xinjun Wang (Molecular Biology Reports, 2022)

Screening and production of dsRNA molecules for protecting Cucumis sativus against Cucumber mosaic virus through foliar application - Qin Mo; Beibei Lv; Yu Sun; Xiao Wu; Lili Song; Run Cai; Xueming Tang (Plant Biotechnology Reports, 2022)

The decreased expression of GW2 homologous genes contributed to the increased grain width and thousand‑grain weight in wheat-Dasypyrum villosum 6VS·6DL translocation lines - Zhiyu Feng; Long Song; Wanjun Song; Zhongqi Qi; Jun Yuan; Run Li; Haiming Han; Huifang Wang; Zhaoyan Chen; Weilong Guo; Mingming Xin; Jie Liu; et al. (Theoretical and Applied Genetics, 2021)

Identification of differentially expressed genes associated with aluminum resistance in the soybean plant - Jing-xuan Wang; Bo Wang; Lu-bin Cui; Hao Xie; Run-zhi Li; Cheng Wang; Zhang-jie Nan; Yu-shu Liu; Jing-yu Ma; Yun-jin Sun; Wei-yu Li (Physiology and Molecular Biology of Plants, 2021)

Mapping and identification of CsSh5.1, a gene encoding a xyloglucan galactosyltransferase required for hypocotyl elongation in cucumber (Cucumis sativus L.) - Keyan Zhang; Junsong Pan; Yue Chen; Ying Wei; Hui Du; Jingxian Sun; Duo Lv; Haifan Wen; Huanle He; Gang Wang; Run Cai (Theoretical and Applied Genetics, 2021)

Synaptic Adaptation Contributes to Stimulus-Specific Adaptation in the Thalamic Reticular Nucleus - Yu-Ying Zhai; Ryszard Auksztulewicz; Pei-Run Song; Zhi-Hai Sun; Yu-Mei Gong; Xin-Yu Du; Jie He; Xiongjie Yu (Neuroscience Bulletin, 2020)

Effects of steel slag amendments on accumulation of cadmium and arsenic by rice (Oryza sativa) in a historically contaminated paddy field - Huaidong He; Qingqing Xiao; Ming Yuan; Run Huang; Xianbin Sun; Xiaomei Wang; Huaiqiong Zhao (Environmental Science and Pollution Research, 2020)

Suppression of miR-30a-3p Attenuates Hepatic Steatosis in Non-alcoholic Fatty Liver Disease - De-Run Wang; Bing Wang; Ming Yang; Zhen-lu Liu; Jing Sun; Yan Wang; Hui Sun; Liang-Jun Xie (Biochemical Genetics, 2020)

A role of age-dependent DNA methylation reprogramming in regulating the regeneration capacity of Boea hygrometrica leaves - Run-Ze Sun; En-Hui Zuo; Jin-Feng Qi; Yang Liu; Chih-Ta Lin; Xin Deng (Functional & Integrative Genomics, 2020)

Seismic risk evaluation for a planning mountain tunnel using improved analytical hierarchy process based on extension theory - Jing-song Xu; Hua Xu; Run-fang Sun; Xiang-wei Zhao; Yin Cheng (Journal of Mountain Science, 2020)

Paeoniflorin inhibits Th1 and Th17 cells in gut-associated lymphoid tissues to produce anti-arthritis activities - Fei Fei; Li-xiang Aa; Qi Qi; Run-bin Sun; Cai-xia Yan; Ji-ye Aa; Guang-ji Wang (Inflammopharmacology, 2019)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Insight into the Dissolution Molecular Mechanism of Ternary Solid Dispersions by Combined Experiments and Molecular Simulations - Run Han; Tianhe Huang; Xinyang Liu; Xunqing Yin; Haifeng Li; Jiahong Lu; Yuanhui Ji; Huimin Sun; Defang Ouyang (AAPS PharmSciTech, 2019)

The jasmonate-responsive transcription factor CbWRKY24 regulates terpenoid biosynthetic genes to promote saponin biosynthesis in Conyza blinii H. Lév. - Wen-Jun Sun; Jun-Yi Zhan; Tian-Run Zheng; Rong Sun; Tao Wang; Zi-Zhong Tang; Tong-Liang Bu; Cheng-Lei Li; Qi Wu; Hui Chen (Journal of Genetics, 2018)

Selective precipitation and characterization of lignin–carbohydrate complexes (LCCs) from Eucalyptus - Bao-Cheng Zhao; Ji-Dong Xu; Bo-Yang Chen; Xue-Fei Cao; Tong-Qi Yuan; Shuang-Fei Wang; Adam Charlton; Run-Cang Sun (Planta, 2018)

Identification and mapping of ts (tender spines), a gene involved in soft spine development in Cucumis sativus - Chunli Guo; Xuqin Yang; Yunli Wang; Jingtao Nie; Yi Yang; Jingxian Sun; Hui Du; Wenying Zhu; Jian Pan; Yue Chen; Duo Lv; Huanle He; et al. (Theoretical and Applied Genetics, 2018)

Efficient and Product-Controlled Depolymerization of Lignin Oriented by Raney Ni Cooperated with Cs x H3 − x PW12O40 - Xiao-Jun Shen; Jia-Long Wen; Pan-Li Huang; Kai Zheng; Shuang-Fei Wang; Qiu-Yun Liu; Adam Charlton; Run-Cang Sun (BioEnergy Research, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Increasing the yield of middle silk gland expression system through transgenic knock-down of endogenous sericin-1 - Sanyuan Ma; Xiaojuan Xia; Yufeng Li; Le Sun; Yue Liu; Yuanyuan Liu; Xiaogang Wang; Run Shi; Jiasong Chang; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2017)

Identification and characterization of multiple porcine astrovirus genotypes in Hunan province, China - Chao-Ting Xiao; Zhang Luo; Sun-Liang Lv; Tanja Opriessnig; Run-Cheng Li; Xing-Long Yu (Archives of Virology, 2017)

Inhibitory effect of estrogen receptor beta on P2X3 receptors during inflammation in rats - Qian Jiang; Wen-xin Li; Jia-run Sun; Tian-tian Zhu; Juan Fan; Li-hua Yu; Geoffrey Burnstock; Hua Yang; Bei Ma (Purinergic Signalling, 2017)

XCI-escaping gene KDM5C contributes to ovarian development via downregulating miR-320a - Yi-Xi Sun; Yi-Xin Zhang; Dan Zhang; Chen-Ming Xu; Song-Chang Chen; Jun-Yu Zhang; Ye-Chun Ruan; Feng Chen; Run-Ju Zhang; Ye-Qing Qian; Yi-Feng Liu; Lu-Yang Jin; et al. (Human Genetics, 2017)

Silencing of HMGA2 promotes apoptosis and inhibits migration and invasion of prostate cancer cells - Zhan Shi; Ding Wu; Run Tang; Xiang Li; Renfu Chen; Song Xue; Chengjing Zhang; Xiaoqing Sun (Journal of Biosciences, 2016)

A Brachypodium distachyon MAPKK Gene BdMKK6.2 Negatively Regulates Drought Stress Tolerance in Transgenic Tobacco Plants - Jiutong Sun; Run Zhou; Yaping Li; Wei Hu; Ding Qiu; Xiatian Wang; Qiong Wang; Zhijuan Feng; Lianzhe Wang; Yi Zhou; Guangyuan He; Guangxiao Yang (Journal of Plant Growth Regulation, 2016)

Engineering geological classification of the structural planes for hydroelectric projects in Emeishan Basalts - Shu-qin Sun; Run-qiu Huang; Xiang-jun Pei; Song-jiang Zhao (Journal of Mountain Science, 2016)

The Synergic Relationship Between Xylan Removal and Enhanced Cellulose Digestibility for Bioethanol Production: Reactive Area, Crystallinity, and Inhibitation - Haiyan Yang; Jinghuan Chen; Qian Chen; Kun Wang; Run-Cang Sun (BioEnergy Research, 2015)

Naturally p-Hydroxybenzoylated Lignins in Palms - Fachuang Lu; Steven D. Karlen; Matt Regner; Hoon Kim; Sally A. Ralph; Run-Cang Sun; Ken-ichi Kuroda; Mary Ann Augustin; Raymond Mawson; Henry Sabarez; Tanoj Singh; Gerardo Jimenez-Monteon; et al. (BioEnergy Research, 2015)

Expression profiles of miRNAs in Gossypium raimondii - Jun Ma; Teng-long Guo; Qing-lian Wang; Kun-bo Wang; Run-run Sun; Bao-hong Zhang (Journal of Zhejiang University-SCIENCE B, 2015)

The Brachypodium distachyon BdWRKY36 gene confers tolerance to drought stress in transgenic tobacco plants - Jiutong Sun; Wei Hu; Run Zhou; Lianzhe Wang; Xiatian Wang; Qiong Wang; Zhijuan Feng; Yaping Li; Ding Qiu; Guangyuan He; Guangxiao Yang (Plant Cell Reports, 2015)

Structural and Hydrolysis Characteristics of Cypress Pretreated by Ionic Liquids in a Microwave Irradiation Environment - Ji-Kun Xu; Yong-Chang Sun; Run-Cang Sun (BioEnergy Research, 2014)

Scale Effects on Spatially Varying Relationships Between Urban Landscape Patterns and Water Quality - Yanwei Sun; Qinghai Guo; Jian Liu; Run Wang (Environmental Management, 2014)

Leaking behavior of shield tunnels under the Huangpu River of Shanghai with induced hazards - Huai-Na Wu; Run-Qiu Huang; Wen-Juan Sun; Shui-Long Shen; Ye-Shuang Xu; Yan-Bin Liu; Shou-Ji Du (Natural Hazards, 2014)

Isolation and Structural Characterization of Lignin Polymer from Dendrocalamus sinicus - Zheng-Jun Shi; Ling-Ping Xiao; Jia Deng; Run-Cang Sun (BioEnergy Research, 2013)

Biodegradation of Lignocellulose by White-Rot Fungi: Structural Characterization of Water-Soluble Hemicelluloses - Ling-Ping Xiao; Zheng-Jun Shi; Yuan-Yuan Bai; Wei Wang; Xue-Ming Zhang; Run-Cang Sun (BioEnergy Research, 2013)

Treatment of Furfural Residue by Solvent Extraction for Enzymatic Hydrolysis: Effect of Delignification on the Structure and Digestibility - Shao-Ni Sun; Xue-Fei Cao; Ming-Fei Li; Feng Xu; Run-Cang Sun (BioEnergy Research, 2013)

Pretreatment of PC12 Cells with 17β-estradiol Prevents Aβ-Induced Down-Regulation of CREB Phosphorylation and Prolongs Inhibition of GSK-3β - Yanxing Chen; Ying Su; Xiaoqin Run; Zhou Sun; Tao Wang; Shenggang Sun; Zhihou Liang (Journal of Molecular Neuroscience, 2013)

Characterization of Lignins Isolated with Alkaline Ethanol from the Hydrothermal Pretreated Tamarix ramosissima - Ling-Ping Xiao; Zheng-Jun Shi; Feng Xu; Run-Cang Sun (BioEnergy Research, 2013)

Unveiling the Structural Heterogeneity of Bamboo Lignin by In Situ HSQC NMR Technique - Jia-Long Wen; Bai-Liang Xue; Feng Xu; Run-Cang Sun (BioEnergy Research, 2012)

Study on canopy disturbance regime and mechanism of tree species diversity maintenance in the lower subtropical evergreen broad-leaved forest, South China - Zang Run-Guo; Wang Bo-Sun (Plant Biosystems, 2002)

Influence of Ca2+ on the thylakoid lumen violaxanthin de-epoxidase activity through Ca2+ gating of H+ flux at the CFo H+ channel - Run-Sun Pan; Richard A. Dilley (Photosynthesis Research, 2000)